Analysis of DNA methylation patterns in the tumor immune microenvironment of metastatic melanoma. Issue 5 (21st March 2020) - Mitra, Shamik; Lauss, Martin; Cabrita, Rita; Choi, Jiyeon; Zhang, Tongwu; Isaksson, Karolin; Olsson, Håkan; Ingvar, Christian; Carneiro, Ana; Staaf, Johan; Ringnér, Markus; Nielsen, Kari; et al.
Abstract : The presence of immune cells in the tumor microenvironment has been associated with response to immunotherapies across several cancer types, including melanoma. Despite its therapeutic relevance, characterization of the melanoma immune microenvironments remains insufficiently explored. To distinguish the immune microenvironment in a cohort of 180 metastatic melanoma clinical specimens, we developed a method using promoter CpG methylation of immune cell type‐specific genes extracted from genome‐wide methylation arrays. Unsupervised clustering identified three immune methylation clusters with varying levels of immune CpG methylation that are related to patient survival. Matching protein and gene expression data further corroborated the identified epigenetic characterization. Exploration of the possible immune exclusion mechanisms at play revealed likely dependency on MITF protein level and PTEN loss‐of‐function events for melanomas unresponsive to immunotherapies (immune‐low). To understand whether melanoma tumors resemble other solid tumors in terms of immune methylation characteristics, we explored 15 different solid tumor cohorts from TCGA. Low‐dimensional projection based on immune cell type‐specific methylation revealed grouping of the solid tumors in line with melanoma immune methylation clusters rather than tumor types. Association of survival outcome with immune cell type‐specific methylation differed across tumor and cell types. However, in melanomas immune cell type‐specific methylation was associated with inferior patient survival. Exploration of the immune methylation patterns in a pan‐cancer context suggested that specific immune microenvironments might occur across the cancer spectrum. Together, our findings underscore the existence of diverse immune microenvironments, which may be informative for future immunotherapeutic applications. Abstract : The importance of the tumor immune microenvironment has been highlighted in multiple cancers, but information regarding the contribution of individual immune cell types is lacking for melanoma. In this study, we have sought to fill the gap by identifying distinct DNA methylation patterns for specifc immune cells. These were corroborated by other molecular correlates and found to be shared across other types of solid tomors.